2022
DOI: 10.1161/jaha.121.024404
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Heart Team Decisions for Patients With Complex Valvular Heart Disease: A Large, Single‐Center Experience

Abstract: Background A multidisciplinary approach might be pivotal for the management of patients with valvular heart disease (VHD), but clinical outcome data are lacking. Methods and Results At our institution, since 2014, internal guidelines recommended heart team consultations for patients with VHD. The clinical/echocardiographic characteristics, treatment recommendations, performed treatment, and early clinical outcomes of consecutive, hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…As much as a quarter of patients presented at their first evaluation in our dedicated adult outpatient clinic with a severe valve dysfunction, that is expected to determine a major impact on the overall CHD hemodynamics. These patients were older, presented with more advanced NYHA functional class and more often had an underlying moderate or severe CHD, in line with recent studies reporting the increasing complexity of ACHD patients (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Moreover, patients with severe VHD were more prone to develop arrhythmias and more often required interventions/reinterventions, confirming previous observations (25)(26)(27).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As much as a quarter of patients presented at their first evaluation in our dedicated adult outpatient clinic with a severe valve dysfunction, that is expected to determine a major impact on the overall CHD hemodynamics. These patients were older, presented with more advanced NYHA functional class and more often had an underlying moderate or severe CHD, in line with recent studies reporting the increasing complexity of ACHD patients (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Moreover, patients with severe VHD were more prone to develop arrhythmias and more often required interventions/reinterventions, confirming previous observations (25)(26)(27).…”
Section: Discussionsupporting
confidence: 88%
“…From the above-mentioned database, we obtained the report of the first clinical outpatient evaluation that included complete medical history, vital signs, electrocardiogram (ECG), complete echocardiography. According to our institutional clinical pathway dedicated to ACHD patients ( 8 ), clinical assessment, ECG reading, and echocardiograms are directly performed and reported from experienced cardiologists specialized in the imaging and care of this patients’ population (FG, AD, and RL) and all patients that require an intervention are discussed in Heart Team, as previously described ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some large studies demonstrated excellent outcomes of patients treated according to the Heart Team recommendations, 18,19 and some authors showed improved outcome of patients with CAD after the implementation of the multidisciplinary evaluation and a Heart Team program 20 . Nevertheless, previous studies focused only on CAD or HVD patients separately, so there is no information on the relative impact of the same Heart Team on different cardiac diseases 21–25 . As a consequence of available evidence, it can be assumed that the Heart Team approach is well tolerated, but it is not possible to determine whether this approach really induces a change in patient management and, if so, the magnitude of this change.…”
Section: Discussionmentioning
confidence: 99%
“…From a traditional face-to-face doctor–patient relationship, we have moved to a modern model in which the patient is now at the centre, with multiple specialists of equal importance sharing expertise and dedicated to the patient. The ‘team approach’ is therefore a reproducible model in every hospital and for every type of disease and specialty to identify the appropriate diagnosis and therapeutic strategy 16–21,25,26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation